Postopertive ACL Reconstruction Treatment Protocol - McBride, M. J.; Hurley, J. A.; Adelman, R. J.; Goldman, R. T.
Postopertive ACL Reconstruction Treatment Protocol Day One - Initial Evaluation Day One - Exercises through week One Week One - Initiate Exercise Week Two Week Three Week Four Week Six throuh Eight Week Eight through Sixteen (4th month)